Allelopathy of garden pea on corn in no-tillage system - Giovanetti, Leonardo Khaoê; Bonome, Lisandro Tomas da Silva; Souza, Edidouglas de; Bittencourt, Henrique von Hertwig; Lanzendorf, Douglas Zin; Tormen, Luciano (Revista de Ciências Agroveterinárias, 2024)
The cover crop selection for the no-tillage system generally does not consider the possible allelopathic effects between species. This study identified and quantified the allelochemicals released by garden pea(Pisum sativumL. ssp. arvense(L.) Poir.) as a cover crop, at different sowing densities (0; 27.5; 55; 82.5 kg ha-1) and decomposition times (7, 21 and 35 days) before sowing corn (Zea mays). Soil allelochemicals were identified and quantified using high-performance liquid chromatography (HPLC). The variables emergence, emergence speed index (ESI), chlorophyll aand b, leaf area, and dry mass were assessed in corn aboveground. There was an increase in catechin with corn cultivation. Epicatechin was identified after corn was sown 21 and 35 days after cutting the garden pea. Resveratrol was associated with the decomposition of the cover crop and was identified when the corn was sown seven days after it was cut. Emergence, ESI, and leaf area were higher in corn sown 21 and 35 days after cutting the gardenpea, a period in which epicatechin was found. The use of garden peaincreased corn chlorophyll aand b. Dry mass production was higher in corn sown sevenand 35 days after cutting the garden pea. Garden peafollowed by corn in a no-tillage system increases the soil levels ofcatechin, epicatechin, and resveratrol. The use of garden peaincreases chlorophyll levels in corn compared to the control (without the cover crop) and increases the leaf area of the corn when sown seven days after cutting the P. sativum(82.5 kg ha-1).